2018
DOI: 10.1186/s12879-018-2954-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported genital warts among sexually-active university students: a cross-sectional study

Abstract: BackgroundGenital warts are one of the most common forms of sexually-transmitted disease, but their epidemiology has yet to be thoroughly elucidated. The present study was designed to shed light on the prevalence of clinically-confirmed, self-reported genital warts (GWs) in a representative sample of the university population.MethodsIn 2015, a cross-sectional survey was conducted on 11,096 individuals approached at the Students Information Bureau where they came to enroll for a university degree course. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Overall, 977 patients and 977 controls were evaluated and the results showed that consistent condom use exerted a protective role against acquiring AGWs, equally in both sexes. 42 The same conclusion was reached by two recent studies that have already been mentioned above, one from Italy 39 and the other from the United Kingdom. 37 Both of these studies were cross-sectional and included approximately 10,000 participants from the general population.…”
Section: Epidemiological Risk Factors Associated With Agw Developmentsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, 977 patients and 977 controls were evaluated and the results showed that consistent condom use exerted a protective role against acquiring AGWs, equally in both sexes. 42 The same conclusion was reached by two recent studies that have already been mentioned above, one from Italy 39 and the other from the United Kingdom. 37 Both of these studies were cross-sectional and included approximately 10,000 participants from the general population.…”
Section: Epidemiological Risk Factors Associated With Agw Developmentsupporting
confidence: 77%
“…Both men and women that reported a same-sex partner in the past 5 years were more likely to report a history of AGWs but, interestingly, this association was no longer significant after adjusting for numbers of sexual partners. So, with the exception of the American study that assessed AGWs prevalence , 48 both the Italian 39 and the British 37 studies found an increased lifetime occurrence of AGWs in MSM and in both MSM and WSW, respectively, regardless of the reason for that association.…”
Section: Epidemiological Risk Factors Associated With Agw Developmentmentioning
confidence: 92%
“…A 2015 cross-sectional survey conducted on 11,096 students aged ≥18 years highlighted differences in sexual behaviors and health habits among between genders. Among those differences, the most notable are a lower frequency of exclusive relationship in males vs females (40.0% vs 57.8%, p < 0.001), an higher mean number of sex partners in males vs females in the last 24 months (1.9 ± 2.3 vs 1.3 ± 1.4, p < 0.001), and lower HPV-vaccination rates in males vs females (1.3% vs 36.8%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of vaccine availability was even lower in medical students from China (11), but it was much higher in students from countries with national HPV vaccination programs (12,13). Studies from Italy have shown that the HPV vaccination rate was much higher in medical students in comparison with the general student population (13,14). It may be assumed that the situation regarding HPV vaccination and knowledge among non-medical Ukrainian students is also worse.…”
Section: Discussionmentioning
confidence: 99%